Sweat Testing and Recent Advances - Gokdemir, Yasemin; Karadag, Bulent Taner (Frontiers in Pediatrics, 2021)
Cystic fibrosis (CF) is the most common life-threatening autosomal-recessive disease of the Caucasians. The sweat test is the main diagnostic test for CF. It is indicated in evaluation of infants with positive CF newborn screening and in individuals with clinical manifestations suggestive of CF. This article describes the classical sweat test method in detail and also provides an overwiew of the recent advances.